2003
DOI: 10.1002/chem.200390050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical and Electrochemical Properties, and Biological Labeling Studies of Cyclometalated Iridium(III) Bis(pyridylbenzaldehyde) Complexes: Novel Luminescent Cross‐Linkers for Biomolecules

Abstract: We report the synthesis, characterization, photophysical, and electrochemical properties of a series of luminescent cyclometalated iridium(III) complexes containing two aldehyde functional groups [Ir(pba)(2)(N-N)](PF(6)) (Hpba=4-(2-pyridyl)benzaldehyde; N-N=2,2'-bipyridine, bpy (1), 1,10-phenanthroline, phen (2), 3,4,7,8-tetramethyl-1,10-phenanthroline, 3,4,7,8-Me(4)-phen (3), 4,7-diphenyl-1,10-phenanthroline, 4,7-Ph(2)-phen (4)). The X-ray crystal structure of complex 1 has been investigated. Upon photoexcita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(60 citation statements)
references
References 66 publications
5
55
0
Order By: Relevance
“…This data suggests that the covalent binding of 12 to STAT3 is unlikely to play a role in the mechanism of action of this complex and is consistent with previous work by Lo and co-workers, who showed that the reaction of an iridium(III) complex, which also contained the 4-(pyridin-2-yl)benzaldehyde Ĉ N ligand, with alanine formed only trace amounts of adducts, thus indicating facile hydrolysis of the imine intermediates. [21] We next performed a STAT3 pull-down assay using A375 cells co-expressing FLAG-STAT3 and STAT3-GFP to investigate whether 12 could inhibit STAT3 dimerization in cells. In the absence of 12, STAT3-GFP co-immunoprecipitated with FLAG-STAT3 (Figure 3 d).…”
Section: Methodsmentioning
confidence: 99%
“…This data suggests that the covalent binding of 12 to STAT3 is unlikely to play a role in the mechanism of action of this complex and is consistent with previous work by Lo and co-workers, who showed that the reaction of an iridium(III) complex, which also contained the 4-(pyridin-2-yl)benzaldehyde Ĉ N ligand, with alanine formed only trace amounts of adducts, thus indicating facile hydrolysis of the imine intermediates. [21] We next performed a STAT3 pull-down assay using A375 cells co-expressing FLAG-STAT3 and STAT3-GFP to investigate whether 12 could inhibit STAT3 dimerization in cells. In the absence of 12, STAT3-GFP co-immunoprecipitated with FLAG-STAT3 (Figure 3 d).…”
Section: Methodsmentioning
confidence: 99%
“…The complexes [Ir(pba) 2 (NN )] + (22) coordinated with different diimine ligands (NˆN) and the aldehydecontaining cyclometallating ligand pba -can react with the primary amine of biomolecules to form an imine that can be readily reduced to a stable secondary amine [58]. X-ray crystallographic studies of the bipyridine complex reveal a separation of ca.…”
Section: Luminescent Labelsmentioning
confidence: 99%
“…The cross-linked avidin conjugates also show longlived and intense luminescence at an energy similar to that of their alanine counterparts. Given the intense photoluminescence of the avidin conjugates, a simple heterogeneous competitive assay for biotin using one of the con- [58] jugates and biotinylated microspheres has been developed. In the assay, immobilised biotin molecules compete with free biotin analyte on binding to the luminescent avidin conjugate.…”
Section: Luminescent Labelsmentioning
confidence: 99%
“…+ (31) coordinated with different diimine ligands (N^N) and the aldehyde-containing cyclometallating ligand pba can react with the primary amine of biomolecules to form a stable secondary amine after reduction [72]. + (N^C = ppy, mppy, mppz, bzq, pq; R = NH 2 , CHO, NCS, NHCO-CH 2 I) (32) [65,73,74].…”
Section: (N^n)]mentioning
confidence: 99%